2006
DOI: 10.1074/jbc.m504988200
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-type Plasminogen Activator Acts as a Cytokine That Triggers Intracellular Signal Transduction and Induces Matrix Metalloproteinase-9 Gene Expression

Abstract: Tissue-type plasminogen activator (tPA), a serine protease well known for generating plasmin, has been demonstrated to induce matrix metalloproteinase-9 (MMP-9) gene expression and protein secretion in renal interstitial fibroblasts. However, exactly how tPA transduces its signal into the nucleus to control gene expression is unknown. This study investigated the mechanism by which tPA induces MMP-9 gene expression. Both wild-type and non-enzymatic mutant tPA were found to induce MMP-9 expression in rat kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
234
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(245 citation statements)
references
References 48 publications
9
234
0
2
Order By: Relevance
“…We then investigated pro-cath-D internalization by LRP1 using MEF that lacked M6P receptors ( Figure 1B Pro-cath-D and ectopic cath-D do not modulate LRP1b-chain tyrosine phosphorylation in fibroblasts The LRP1 at the plasma membrane is located in clathrin-coated pits and lipid rafts (Boucher et al, 2002;Zhang et al, 2004;Wu and Gonias, 2005), and it has been suggested that there are LRP1-induced signal transduction pathways triggered by tyrosine phosphorylation or RIP in lipid rafts (Boucher et al, 2002; von Cathepsin D, endocytosis and LRP1 RIP D Derocq et al Arnim et al, 2005;Wu and Gonias, 2005). We observed that LRP1b overproduction directs pro-cath-D to the lipid rafts (Beaujouin et al, 2010), suggesting that cath-D modulates the tyrosine phosphorylation of LRP1, as shown for the PDGF-BB (Boucher et al, 2002;Loukinova et al, 2002;Boucher and Gotthardt, 2004;Newton et al, 2005) and CTGF (Yang et al, 2004) growth factors, the tPA serine protease (Hu et al, 2006) and in fibroblasts transformed with v-Src (Barnes et al, 2001(Barnes et al, , 2003. We next investigated the effect of pro-cath-D on the tyrosine phosphorylation of LRP1b in fibroblasts.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…We then investigated pro-cath-D internalization by LRP1 using MEF that lacked M6P receptors ( Figure 1B Pro-cath-D and ectopic cath-D do not modulate LRP1b-chain tyrosine phosphorylation in fibroblasts The LRP1 at the plasma membrane is located in clathrin-coated pits and lipid rafts (Boucher et al, 2002;Zhang et al, 2004;Wu and Gonias, 2005), and it has been suggested that there are LRP1-induced signal transduction pathways triggered by tyrosine phosphorylation or RIP in lipid rafts (Boucher et al, 2002; von Cathepsin D, endocytosis and LRP1 RIP D Derocq et al Arnim et al, 2005;Wu and Gonias, 2005). We observed that LRP1b overproduction directs pro-cath-D to the lipid rafts (Beaujouin et al, 2010), suggesting that cath-D modulates the tyrosine phosphorylation of LRP1, as shown for the PDGF-BB (Boucher et al, 2002;Loukinova et al, 2002;Boucher and Gotthardt, 2004;Newton et al, 2005) and CTGF (Yang et al, 2004) growth factors, the tPA serine protease (Hu et al, 2006) and in fibroblasts transformed with v-Src (Barnes et al, 2001(Barnes et al, , 2003. We next investigated the effect of pro-cath-D on the tyrosine phosphorylation of LRP1b in fibroblasts.…”
Section: Resultssupporting
confidence: 69%
“…It delivers most, but not all, of these ligands to lysosomes for degradation (Herz and Strickland, 2001;Gonias et al, 2004;Emonard et al, 2005;May et al, 2007). It has also been shown that LRP1 is involved in signal transduction by phosphorylation of the tyrosine in the cytoplasmic NPXY motifs of its b-chain and modulation of signaling pathways such as the MAP kinase pathway (Barnes et al, 2001(Barnes et al, , 2003Boucher et al, 2002;Boucher and Gotthardt, 2004;Loukinova et al, 2002;Yang et al, 2004;Newton et al, 2005;Hu et al, 2006). More recent studies have shown that LRP1 influences gene transcription by regulated intramembrane proteolysis (RIP) of its b-chain (May et al, 2002;Kinoshita et al, 2003;von Arnim et al, 2005;Zurhove et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence suggests t-PA can act as a cytokine and binds to the cell membrane receptor low-density-lipoprotein receptor-related protein-1 (LRP-1). Independent of its proteolytic capacity, binding by t-PA to LRP-1 induces receptor tyrosine phosphorylation, triggers intracellular signal transduction, and induces collagen production by fibroblasts (30)(31)(32)(33). We detected LRP-1 expression in nasal tissue by real-time PCR, and there was no significant difference between UT and NPs from control subjects and patients with CRS(data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…A number of studies have shown that the role of tPA is far more complex, and as a result, the functional role of tPA has been dramatically revised. It is now believed that tPA also plays an important, plasmin-independent, stimulatory, cytokine-like role responsible for a diverse number of physiological functions, including the regulation of endothelial cell proliferation (13), modulation of neuron apoptosis (14), and transcriptional up-regulation of MMP9 (10,11). It must be said, however, that the multifarious plasmin-dependent and -independent functions of tPA are not mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…tPA is known to signal as a cytokine via LRP, causing increased transcription of MMP9 (10,11). RT-PCR was carried out to assess mesangial cell expression of MMP9 and MMP2 mRNAs in response to ACE-I treatment.…”
Section: Resultsmentioning
confidence: 99%